La tarea de reconocer el multiculturalismo colombiano (2009)
Since the Constitution of 1991 established that Colombia is a multiethnical and pluricultural country, there is a growing interest about the multiculturalist issue among academic and political sectors. These investigations describe the history of the ignorance about the cultures of Colombia and examines today´s tension lived by the colombian State, which, in his task of fighting for the liberty and equality of the citizens, it has to recognise also the colective rights. The colombian experience shows the limits of the liberal legislation based traditionallly on individual rights and gives us a context for the discussion about the role of the State in the issue of the colective rights. The moral philosophers that supportcomunitarism and the ones that support the universality of the human rights have recently focussed on this issue.Key words:Plurality, culture, Colombia, law, native, participation, recognition, Constitution.